Relationship of internal institutions, knowledge sharing, and technological innovation in characteristic cultural enterprises: Evidence from China. (29th August 2022) - Liu, Lingyan; Lin, Minghua; Yu, Ming
Abstract : The paper empirically studies the relationship between internal institutions, knowledge sharing, and technological innovation based on the data of investigating 163 China's characteristic culture enterprises by applying structural equation model. The study shows that the internal institution of characteristic cultural enterprises can significantly enhance the knowledge sharing of employees in characteristic cultural enterprises; the knowledge sharing of employees will significantly enhance the technical innovation level of characteristic cultural enterprises; the internal institution of characteristic cultural enterprises does not directly and significantly improve the technical innovation level, but indirectly through enhancing the knowledge sharing of enterprise employees.